2007
DOI: 10.1080/09663690701659150
|View full text |Cite
|
Sign up to set email alerts
|

‘Bad Mothers’ and ‘Delinquent Children’: Unravelling anti-begging rhetoric in the Ecuadorian Andes

Abstract: In this paper I examine the rhetorics that circulate surrounding the lives of young indigenous women and children who beg on the streets of Quito, Ecuador. I focus particularly on rhetorics being produced and reproduced by urban planners, social workers, religious leaders and the media. Drawing on in-depth interviews, I reveal how these groups regularly imagine indigenous women and children in terms of child exploitation/child delinquency, false manipulation of public sympathies, ignorance, laziness and filth.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
6

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 33 publications
0
21
0
6
Order By: Relevance
“…Thirteen of the papers were in 'human geography' journals and/or published by authors who identified as geographers in their institutional affiliation (Abebe, 2007; 2008; Aitken et al, 2006;Bromley and Mackie, 2008;Dyson, 2008;Evans, 2006;Hastadewi, 2009;Jennings et al, 2006;Robson et al, 2006;Swanson, 2007;van Blerk, 2007;. Within the limitations of the database search parameters, this observation suggests that geographers have published, with some regularity, on research with working children in the Majority World.…”
Section: A Review Of the Literature On Children's Workmentioning
confidence: 99%
“…Thirteen of the papers were in 'human geography' journals and/or published by authors who identified as geographers in their institutional affiliation (Abebe, 2007; 2008; Aitken et al, 2006;Bromley and Mackie, 2008;Dyson, 2008;Evans, 2006;Hastadewi, 2009;Jennings et al, 2006;Robson et al, 2006;Swanson, 2007;van Blerk, 2007;. Within the limitations of the database search parameters, this observation suggests that geographers have published, with some regularity, on research with working children in the Majority World.…”
Section: A Review Of the Literature On Children's Workmentioning
confidence: 99%
“…Begging itself generally refers to a public request for money, food, or other goods, with little or nothing of value given in return (Lankenau, ,b; Snow & Anderson, ; Van Houcke, ). It is also generally agreed that this non‐reciprocated gift places the beggar outside the gift‐exchange theory structure (Swanson, ). This asymmetrical relationship places the beggar in an awkward position.…”
Section: Beyond the Theoretical Paradoxesmentioning
confidence: 99%
“…In the urban Latin American context, the influence of neoliberalism is tangible in the (re)definition and governance of public space. The implementation of various policies – from gentrifying historical centres and ‘whitening’ their users to slum upgrading to the operationalization of ‘iron fist’ policies to halt criminality – have reordered relations between the citizenry, the (international) private sector and the state (Hume, 2007; Swanson, 2007; Aguiar, 2009; Nuijten & Koster, 2012). Zero‐tolerance policies, including various ‘wars’ on drugs, piracy and delinquency, have mushroomed all across the region, often functioning as part of programmes to enforce the regime of legality engendered by neoliberalism.…”
Section: Neoliberal Ideology and The Changing Definition Of Illegal Mmentioning
confidence: 99%